Characterization of temperature difference between the neighbouring days in China and its potential driving factors. (1st May 2019) - Tian, Peipei; Lu, Hongwei; Xue, Yuxuan
Abstract : Understanding the temperature difference between neighbouring days (TDN) is beneficial for reducing the harmful impacts of sudden temperature changes on human health and establishing adaptation policies considering global TDN characteristics. This study analyses the spatiotemporal characteristics of TDN in Mainland China on the basis of the daily observation data from 839 stations in 1961–2017. Results show that the TDN increases with the latitude from south to north. Meanwhile, TDN in winter is higher but lower in summer. These characteristics potentially arise from the variations in solar elevation angle, that is, a decreased TDN corresponds to an increased solar elevation angle in most parts of China. Areas with high solar elevation angle are usually characterized by low TDN, which implies that temperature is stable for neighbouring days in areas with high solar elevation angle. Moreover, the variation rate of the annual mean TDN is negative in most parts of China, especially in the north. These findings are expected to provide an overview of the spatiotemporal characteristics of TDN and support future studies on the impacts of TDN variations on regional environmental changes. Abstract : The TDN decreases with increasing the solar elevation angle in a large scale.